Pemberdayaan Masyarakat Desa Melalui Pelatihan Keterampilan Kerajinan Tangan Untuk Meningkatkan Ekonomi Lokal - Sholikin Hasan; Linna Endah Nur Wahyuni; Joko Widodo; Imam Fatoni (https://journal.metanusantara.com/impact/index.php/jpk, 2024)
Empowering rural communities through handicraft skills training has become one of the effective strategies in improving the local economy. In the midst of economic challenges faced by rural communities, skills development based on local potential can provide sustainable business opportunities. This research uses a qualitative approach with the Participatory Action Research (PAR) method, which involves the community as an active subject in the research. The main data sources were obtained through in-depth interviews, participatory observations, and focus group discussions (FGDs) with trainees, instructors, and policy makers in Mlowokarangtalun Village Pulokulon Grobogan.The purpose of this study was to analyse the impact of handicraft skills training on improving the economy of the village community and identify supporting and inhibiting factors in the implementation of this empowerment programme. The results showed that skills training based on inorganic waste utilisation was able to increase participants' income from an average of Rp1,000,000 to Rp2,500,000 per month. In addition, there are significant social changes, such as increased independence, self-confidence, and active participation in the community. These results are in line with the concept of empowerment, which emphasises the active participation of the community in the process of local economic development